2020
DOI: 10.26496/bjz.2014.61
|View full text |Cite
|
Sign up to set email alerts
|

Rose-ringed parakeet (Psittacula krameri) and starling (Sturnus vulgaris) syntopics in a Mediterranean urban park: evidence for competition in nest-site selection?

Abstract: Introduced species may compete with indigenous ones, e.g. for space resources, but evidence for syntopic cavity-nester birds is limited, at least for Mediterranean urban parks. In this work we report data on nest-site habitat use, availability and selection in two species: the introduced rose-ringed parakeet (Psittacula krameri) and the autochthonous starling (Sturnus vulgaris) nesting in ornamental tree (Cedrus libanotica) patches occurring in an historical urban park (Rome, central Italy). In particular, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…We visually estimated the height of the cavity above ground (in m) and the width of its entrance (in cm), which was scored as small, medium or large (less than 4 cm, 4-8 cm and greater than 8 cm, respectively) [16]. We did not consider the orientation of the cavities [16], as in other studies on nest-site competition between parakeets and native species [14,15,[17][18][19], because orientation did not affect the selection of cavities in a previous study [13]. Our previous analyses showed a preference of both parakeets and noctules for cavities well above ground (approx.…”
Section: Population Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…We visually estimated the height of the cavity above ground (in m) and the width of its entrance (in cm), which was scored as small, medium or large (less than 4 cm, 4-8 cm and greater than 8 cm, respectively) [16]. We did not consider the orientation of the cavities [16], as in other studies on nest-site competition between parakeets and native species [14,15,[17][18][19], because orientation did not affect the selection of cavities in a previous study [13]. Our previous analyses showed a preference of both parakeets and noctules for cavities well above ground (approx.…”
Section: Population Monitoringmentioning
confidence: 99%
“…Thus, this species has been the subject of several reviews on ecological impacts [7,8] and of systematic risk assessments [9,10]. Some studies have assessed the negative impacts of rose-ringed parakeets on native birds through competition for food in bird feeders, where parakeets disrupt the foraging behaviour of native birds [11,12], and for nest sites of several cavity-nesting birds [13][14][15][16][17][18][19]. However, as in other invasive bird species for which information is available, these studies only indicate impacts on the individual fitness of native birds.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, rose-ringed parakeets exhibit exponential population growth and aggressive range expansion has been recorded (Nebot 1999;Butler 2003;Kleunen et al 2010;Dodaro and Battisti 2014).…”
Section: Introductionmentioning
confidence: 82%
“…Multiple studies from the Netherlands, Germany and France have also reported aggressive interactions with native cavity-nesters including bats but failed to find any evidence of population-level impacts (Clergeau and Vergnes, 2009;Czajka et al, 2011;Tamis, 2015). In southern Europe, there is some evidence that Ring-necked Parakeets compete locally with native cavity-nesters such as Common Starlings (Sturnus vulgaris; Dodaro and Battisti, 2014) and Lesser Kestrels (Falco naumanni; Hernández-Brito et al, 2014a), rats (Rattus rattus; Hernández-Brito et al, 2014b) and squirrels (Sciurus vulgaris; . Probably the best documented case of impact on a native cavity-nester is from Seville, Spain, where Hernández-Brito et al (2018) reported that Ring-necked Parakeets compete with a threatened bat species, the greater noctule (Nyctalus lasiopterus).…”
Section: Impactsmentioning
confidence: 99%